Euripides, Antigone fr. 163 K: exegesis and hypothesis of contextualization - Moles, Francesco (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2026)
The paper takes into examination the character of Antigone in Euripides’ Antigone by comparing it to the character of Sophocles’ homonymous tragedy and of Euripides’ Phoenissae. In particular, it is offered an exegetical note, with hypothesis of contextualization, of fr. 163 K., which has often been neglected in the studies about Euripides’ Antigone due to its not very clear interpretation and the difficulties to frame it in the uncertain plot of the play.